Investigating the feasibility of implementing microbially induced calcite precipitation to stabilize sand, clay and gold tailings - Hyde, Rhonda (Department of Civil Engineering, 2023)
Microbially Induced Calcite Precipitation (MICP) is an emerging bio-mediated technology which has been successfully applied in soil improvement research. MICP uses the enzyme urease produced from bacteria to breakdown urea into carbonate ions. These carbonate ions combine with free calcium ions to form calcium carbonate, which acts as a bio-cement. MICP presents a unique, sustainable soil improvement solution to the pressing issues resulting from tailings impoundment failures. It has shown potential through increasing shear strength and decreasing porosity in soils. However, MICP applications in soil improvement outside erosion mitigation in granular soils remain limited. This is similar to the limited use of injection treatment, in comparison to the more prevalent spraying and surface percolation in MICP applications. This research focused on the efficacy of the developed injection procedure for administering the MICP treatment to increase shear strength and decrease porosity in sand, clay and gold tailings at greater depths and evaluating its feasibility. By determining the efficacy and significance of the treatment in improving the geotechnical characteristics of the soil samples, the methodology can be evaluated for its application as a soil improvement technique. Results showed successful cementation of the particles of the soils tested with an increase in cohesion of 7.7% and 23.1% for clay, and tailings respectively and an infinite increase in the apparent cohesion of sand from 0 to 20kPa. The response to MICP treatment in terms of the angle of internal friction were inconclusive, where a decrease was observed across the board. This was attributed to complex stress-strain behaviour as well as the particle morphology. A decrease in porosity of approximately 26% in clay and 8% in tailings was observed, whilst sand had an increase of approximately 3%. The increase in porosity in sand was identified as a result of the erosion of the coarse uncemented particles during treatment. The results emphasised the greater success of MICP treatment in more granular soils, with sand achieving the greatest improvement with regard to the apparent cohesion and particle density. Characteristically, the particle sizes of the gold tailings fell between the fine clay and the coarse sand which was reflected in the response of the gold tailings to treatment. Overall, sand had the greatest increase in shear strength, followed by the gold tailings and lastly the clay. The gold tailings contained a higher percentage of fines than the sand, illustrating the limitation of MICP applications in fine grained soils. However, the predominant coarse fraction allowed for an overall increase in the shear strength parameters in the gold tailings. An evaluation of the feasibility shows that the methods provide a scalable soil improvement technique in stabilisation applications in contrast to existing MICP surface treatments in sands. In clays and tailings however, interactions of heavy metals with the microbial community as well as the particle size limit the efficacy of MICP. In conclusion, MICP is found to be a feasible soil improvement technique in stabilising gold tailings with the consideration of the impact of heavy metals and the particle size on the efficacy of the treatment.